Prognostic value of nutritional status in patients with human immunodeficiency virus infection-related lymphoma - Liu, TingTing; Hu, RenZhi; Lv, Jing; Luo, Qin; Xu, LuXiang; Wang, ChaoYu; Liu, Jun; Yang, ZaiLin; Xu, LingLi; Liu, Yao (Frontiers in Nutrition, 2022)
Objective: To investigate the predictive value of nutritional status on the prognosis of patients with human immunodeficiency virus (HIV) infection-related lymphoma. Methods: A total of 149 patients with HIV infection-related lymphoma as research subjects. Based on patient prognosis, they were divided into a poor prognosis group (n=30) and a good prognosis group (n=119). General data from patients in both groups were collected, and the nutritional status of the patients was evaluated using the Controlling Nutritional Status (CONUT) score. Factors affecting the prognosis of HIV infection-related lymphoma were analyzed by univariate and multivariate analyses, and a prediction model was developed based on the analyzed factors. The ROC curve was used to analyze the prediction model of the CONUT score alone and included the CONUT score in the prognosis of HIV infection-related lymphoma patients. The predictive value of the data was assessed, and a survival curve was drawn to compare the survival of patients with different nutritional statuses. Results: There were significant differences in age, B symptoms, treatment conditions, IPI, pathological stage, ECOG PS, CD4+ cell count, β2 microglobulin, and LDH between the poor prognosis group and the good prognosis group (P<0.05). The CONUT score of the poor prognosis group was higher than that of the good prognosis group (P<0.05). The ROC curve was used to analyze the predictive value of the CONUT score alone and the predictive model including the CONUT score on the prognosis of HIV infection-related lymphoma patients. The predictive value of the prognosis of tumor patients was higher (P<0.05). According to the results of the ROC curve analysis, the patients were divided into a high CONUT group (CONUT>6.00 points, n=31) and a low CONUT group (CONUT≤6.00 points, n=118) based on the Optimum threshold of the CONUT score. The survival curve showed that the survival rate of the high CONUT group was lower than that of the low CONUT group (P<0.05). Conclusion: The HIV infection-related lymphoma is related to nutritional status, which is an independent risk factor affecting the prognosis of patients and can be used as a practical indicator to predict the prognosis of patients.